Effects of sidewall MOS channel on performance of AlGaN/GaN FinFET - Son, Dong-Hyeok; Jo, Young-Woo; Sindhuri, V.; Im, Ki-Sik; Seo, Jae Hwa; Kim, Yong Tae; Kang, In Man; Cristoloveanu, Sorin; Bawedin, Maryline; Lee, Jung-Hee (ELSEVIER, 2015)
AlGaN/GaN FinFETs with various fin widths (W-fin), which have both a 2DEG channel and two sidewall MOS channels, have been fabricated by using electron-beam lithography and subsequent sidewall wet etch in tetramethyl ammonium hydroxide (TMAH) solution. The devices with wide W-fin of 150 nm showed normally-on operation with threshold voltage (V-th) of -2.5 and -5.0 V, respectively. The devices also exhibited broad transconductance (g(m)), and excellent off-state performance with very low subthreshold swing (SS). On the other hand, narrow device with W-fin, of 50 nm exhibited normally-off operation with V-th of 3.0 V, but degraded SS due to trapping effect at the sidewall of fin. (C) 2015 Elsevier B.V. All rights reserved.